The Changing Concept of Employment : the Special Connection Between Labour Law and Civil Law in Hungary - Zaccaria, Márton Leó (Warsaw Forum of Economic Sociology, 2015)
The Hungarian labour law reform is a good example of how the idea of flexicurity is enforced in the 21st century in a post-socialist country. Flexible employment relationships overshadow the social side what is necessary in order to develop effectiveness and competitiveness. This process is completed by the relationship between labour and civil law and it is traced back to the special tradition of legal history. The present study surveys the main connection between labour and civil law and gives some remarks on the special private law-nature of labour law. This paper deals with one of the central questions of the Hungarian labour law reform, that is, the changing relationship between labour and civil law. This legal problem can be observed in Hungarian law for a long time. The study focuses on the civil law-type of the employment relationships and the differences between them. This study examines the regulation before 1st July of 2012 with the aim that development will be seen clearly in connection with the regulation in force. The study emphasizes what kind of fundamental changes the direct usage of civil law can perform in the strict structure of employment relationships.